Falsafah penyelidikan pendidikan dari perspektif Islam : konsep dan matlamat - Hashim, Rosnani (Yayasan Takmir, 2004)
This article is a conceptual attempt to define the philosophy of educational research from the Islamic perspective. It delineates the importance of thinking and investigation in the Islamic tradition, the concept and goal of research, the relationship between research and educational theory and practice, and finally, it deals with the issues of research in Islamic Education. This article highlights that a major issue of educational research is an over emphasis of the empirical methods which seem to also influence research in Islamic education and that there is a neglect over the Qur'an as an important source of knowledge. The article calls for a more balanced approach of educational research that employs the empirical, the interpretive, and the normative-critical methods with principles from the Qur'an as the guiding light in understanding the personality, psycho-social and historical development of man in order for educational research to become more meaningful and to inform educational practice.